Risk factors of neuroblastoma: a systematic review and meta-analysis - Onyije, Felix M.; Dolatkhah, Roya; Olsson, Ann; Bouaoun, Liacine; Schüz, Joachim (Frontiers in Public Health, 2025)
IntroductionNeuroblastoma (NB) is the most common extracranial tumor in children. Synthesizing and elucidating modifiable risk factors is fundamental to inform primary prevention of NB. The objective is to review literature and synthesize risk factors for NB.MethodsPubMed, Web of Science, and Embase databases were searched using lists of key words and MeSH terms related to exposures and risk of NB. Studies were included if they were case-control or cohort studies of children under the age of 20 years at diagnosis and reported Relative Risks (RRs) with 95% confidence intervals (CIs). Pooled effect sizes (ES) and 95% CIs for risk factors associated with NB were estimated using random-effects models.ResultsWe included 50 eligible studies from Asia, Europe, and North America, and Oceania on cases of NB diagnosed between 1964 and 2016. We observed associations for maternal occupational exposure to pesticides during preconception/pregnancy (ES 1.62, CI 1.04–2.54), high birthweight [(>4,000 g) ES 1.21, CI 1.02–1.42], and Cesarean section (ES 1.14, CI 1.00–1.30) and the risk of NB. Parental smoking showed a weak association, while breastfeeding ≥6 months (ES 0.50, CI 0.30–0.84) was inversely associated with NB. Birth characteristics such as low birthweight (<2,500 g), small and large-for-gestational age, gestation age <37 weeks and gestation age >40 weeks, and assisted reproductive technology were not associated with NB. Similarly, no associations were suggested for parental age, gestational diabetes, and pre-eclampsia. Maternal alcohol consumption during preconception/pregnancy, maternal intake of vitamin and folic acid during pregnancy, paternal occupational exposure to extremely low-frequency magnetic fields (ELF-MF), and maternal X-ray exposure during pregnancy were also not associated with the risk of NB. Paternal occupational and child's postnatal exposure to pesticides were also not associated with NB.DiscussionThis systematic review and meta-analysis suggest that maternal occupational exposure to pesticides during preconception/pregnancy, high birthweight, Cesarean section, and breastfeeding (beneficial) were associated with the risk of NB, but all associations were rather modest in strength. Synthesizing of these risk factors are needed to inform whether there are avenues for primary prevention of NB.